Vol 2 No 1 EKONOMI KERAKYATAN DALAM PERSPEKTIF EKONOMI SYARI'AH: STRATEGI PENDISTRIBUSIAN DAN PENDAYAGUNAAN ZAKAT PRODUKTIF PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN KENDAL - Solekhan, Ahmad (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2024)
The productive zakat distribution strategy by BAZNAS is an effort to channel wealth from muzzaki to mustahik and then hopefully increase business income and economic welfare for the community. Therefore, Muslims need to know that the productive zakat distribution strategy is carried out by BAZNAS Kendal Regency. It is hoped that this can increase the business capital they have been working on so far, so that in the future they will not only fulfill their daily needs, but also increase their business. If BAZNAS manages productive zakat well, it will have an impact on economic welfare so that the mustahik's standard of living will increase. In channeling business capital to mustahik, of course, looking at the existing budget, the more muzzaki who give zakat infaq shodakoh, the greater the amount of business capital they will receive, this hope and reality is what zakat institutions and mustahik want. This research was conducted using qualitative methods and using qualitative descriptive analysis tools. Test the validity of the data using triangulation. Then data collection techniques using interviews, observation and documentation. The source sample was determined purposively, namely the Kendal Regency BAZNAS Utilization and Distribution division as well as staff and mustahik recipients of productive zakat fund empowerment assistance. The results of the research show that the distribution of productive zakat on mustahik economic empowerment carried out by BAZNAS Kendal Regency was poured into several programs which then formed 4 types of pentasharufan or productive zakat utilization, namely: 1) Providing individual business capital assistance 2) Job skills training 3) assistance group capital 4) Assistance with business facilities and infrastructure. The zakat distribution strategy in the BAZNAS program is analysis through planning, organizing, implementing, monitoring, as well as accuracy of program targets, program socialization, program objectives, program monitoring, as well as integrating organizational goals and formulating them into missions.